Ozone-Induced Optical Density Change of NiO Thin Films and Their Applicability as Neutral Optical Density Filter - R. Noonuruk; N. Wongpisutpaisan; P. Mukdacharoenchai; W. Techitdheera; W. Pecharapa (My University, 2011)
Nickel oxide (NiO) thin films were deposited onto glass substrates by sol-gel spin-coating technique. The coating solution was prepared by reacting nickel acetate tetrahydrate as precursor and absolute ethanol as solvent. The asdeposited films were annealed in air at 350oC. The color of the film can be changed from bleach color to be dark brownish after UV/ozone treatment. The change in optical density of more than 40% can be achieved after 5 min of treatment. The colored films can be readily recovered by thermal treatment at 150 °C within 30 min. Further increasing ozone exposure time leads to greater change in optical density. The presence of ozone-induced hydroxyl groups causes the color change of the films. The unique behavior of this chromic material can be applied as novel tunable neutral optical density filters and related devices by ozone-assisted method.
Keywords: Non-blocking I/O; Nickel oxide; Bleach; Tetrahydrate; Spin Coating; Thermal Treatment; Transition Metal Oxide Nanomaterials